UPAYA PREVENTIF MENGATASI KONFLIK KEKURANGHARMONISAN HUBUNGAN SUAMI ISTERI BERDASARKAN NILAI PENDIDIKAN AL-QUR’AN (STAI Darussalam Lampung, 2023)
The background of the author discusses this issue because of the complexity of marriage conflicts in the domestic life causing disharmony of husband-wife relationships. Sources of family conflicts can be attributed to economic factors, suspicions about infidelity, children, parenting, and family members of a husband or wife. Factors of failure or frustration of the husband or wife at work can also be ventilated into family life. As well as negative behavior of children acquired from association in school and community, will lead to family tension and others. The purpose of writing this problem is to know the preventive efforts to overcome the conflict of disharmony husband-wife relationship in the perspective of al-Qur’an. This type of research is a research library (library research), and the form of research descriptive research that qualitative. Then the data relating to the studied is described and analyzed by using contents analysis or document analysis that is systematic or note-record or document as data source. The results found in the preventive effort to overcome the harmony of husband-wife relationship, namely: to prevent better than to treat, the openness in communication and courtesy, the need for mutual understanding, mutual trust, mutual open, honest with each other and smooth communication, sharing with a partner, caring, or respecting and respecting, husband and wife can perform their own roles and duties, husband and wife try to solve their own problems, have maturity in addressing hausehold problems, fulfilment of material needs, give advice or opinion can encourage both husbands and wives to fear Allah SWT and realize that the mistakes will be tortured on the day of judgment